GOOD CORPORATE GOVERNANCE TERHADAP HARGA SAHAM PADA PERUSAHAAN SEKTOR FOOD AND BEVERAGE YANG TERDAFTAR DI BEI - Mutia Azila; Mohammad Makrus; Nur Hidayati (Universitas Sarjanawiyata Tamansiswa, 2023)
This research aims to determine the influence of Good Corporate Governance on share prices in food and beverage sector companies listed on the IDX for the 2020-2022 period. The independent variables used are the audit committee, institutional ownership, and managerial ownership. The data used in this research are secondary data, namely financial report data published via the www.idx.co.id website and share price data via the websites www.idnfinancials.com and id.investing.com for the 2020-2022 period. The data collection method uses a purposive sampling method. The total sample in the research consisted of 28 companies. The analysis techniques used in this research include descriptive statistics, classical assumption tests, multiple linear regression analysis, and hypothesis testing. The research results show that the audit committee, institutional ownership, and managerial ownership simultaneously influence stock prices. Partially, institutional ownership and managerial ownership have an effect on share prices, while the audit committee has no effect on share prices